Perlindungan Hukum Bagi Korban Pemerkosaan Sedarah yang Melakukan Aborsi Ditinjau dari Hak Asasi Perempuan - Eka Gita Yunita; Mukhamad Bahrul Ulum (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research aims to identify cases of rape victims committed by blood parties where the victim has experienced pregnancy and followed by abortion, this research will be reviewed through Women's Human Rights. Women are entitled to receive justice and legal protection by the government. Abortion or better known by its legal term, abortus procatus which in Latin has the meaning and meaning of deliberate abortion of the womb. Abortion is one of the many health cases that claim many victims, abortion is also one of the health cases included in the criminal act. Criminal regulation of abortion is not without reason, this is done one of them with the aim of saving women's health. Departing from one of the cases that occurred in the community, especially in Batang hari district, where the victim was raped by her own biological brother to experience pregnancy and abortion. The research method used in this study uses normative research using legal norms using a case approach. The results can be concluded that all forms of legal provisions regarding abortion, stating that the act of abortion is not allowed unless there are certain indications that allow it. So that there needs to be legal corrective action related to abortion, especially in certain conditions in order to create a sense of security and justice for others.